The genus Chrysanthemum: Phylogeny, biodiversity, phytometabolites, and chemodiversity - Hao, Da-Cheng; Song, Yanjun; Xiao, Peigen; Zhong, Yi; Wu, Peiling; Xu, Lijia (Frontiers in Plant Science, 2022)
The ecologically and economically important genus Chrysanthemum contains around 40 species and many hybrids and cultivars. The dried capitulum of Chrysanthemum morifolium (CM) Ramat. Tzvel, i.e., Flos Chrysanthemi, is frequently used in traditional Chinese medicine (TCM) and folk medicine for at least 2,200 years. It has also been a popular tea beverage for about 2,000 years since Han Dynasty in China. However, the origin of different cultivars of CM and the phylogenetic relationship between Chrysanthemum and related Asteraceae genera are still elusive, and there is a lack of comprehensive review about the association between biodiversity and chemodiversity of Chrysanthemum. This article aims to provide a synthetic summary of the phylogeny, biodiversity, phytometabolites and chemodiversity of Chrysanthemum and related taxonomic groups, focusing on CM and its wild relatives. Based on extensive literature review and in light of the medicinal value of chrysanthemum, we give some suggestions for its relationship with some genera/species and future applications. Mining chemodiversity from biodiversity of Chrysanthemum containing subtribe Artemisiinae, as well as mining therapeutic efficacy and other utilities from chemodiversity/biodiversity, is closely related with sustainable conservation and utilization of Artemisiinae resources. There were eight main cultivars of Flos Chrysanthemi, i.e., Hangju, Boju, Gongju, Chuju, Huaiju, Jiju, Chuanju and Qiju, which differ in geographical origins and processing methods. Different CM cultivars originated from various hybridizations between multiple wild species. They mainly contained volatile oils, triterpenes, flavonoids, phenolic acids, polysaccharides, amino acids and other phytometabolites, which have the activities of antimicrobial, anti-viral, antioxidant, anti-aging, anticancer, anti-inflammatory, and closely related taxonomic groups could also be useful as food, medicine and tea. Despite some progresses, the genetic/chemical relationships among varieties, species and relevant genera have yet to be clarified; therefore, the roles of pharmacophylogeny and omics technology are highlighted.